2007
DOI: 10.1177/1527002506296545
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Balance and Game Attendance in Major League Baseball

Abstract: This article tests for the effects of a change in competitive balance on attendance at Major League Baseball games using game-level attendance data for the 2000-2002 seasons. Employing the difference between the winning percentages of the home and visiting teams as a measure of competitive balance, the authors find (a) the effects of a change in competitive balance on attendance are not symmetric, (b) the effects of a change in competitive balance increase as a team falls further behind the divisional leader, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…A dummy variable (NIGHT) for whether the game is a night game is included to see if there is any difference between night and day games (Davis 2009). The separate dummy variable for each day, SUNDAY through FRIDAY is also included to control the day-of-the-week effect on the attendance (Meehan et al 2007). We exclude SATURDAY to avoid the possible linear combinations among the variables.…”
Section: Model Specificationmentioning
confidence: 99%
See 3 more Smart Citations
“…A dummy variable (NIGHT) for whether the game is a night game is included to see if there is any difference between night and day games (Davis 2009). The separate dummy variable for each day, SUNDAY through FRIDAY is also included to control the day-of-the-week effect on the attendance (Meehan et al 2007). We exclude SATURDAY to avoid the possible linear combinations among the variables.…”
Section: Model Specificationmentioning
confidence: 99%
“…The studies by Knowles et al (1992) and Rascher (1999), find a positive correlation between competitive balance and game attendance. Meehan et al (2007) found that fans do respond to changes in competitive balance: a change in competitive balance was found to have a positive effect on attendance if the home team had a better win percentage than the visiting team, and an insignificant effect if the visiting team had a winning percentage than the home team. Results found by Lemke et al (2009) did not support the outcome hypothesis.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, some studies supporting the conventional uncertainty of outcome hypothesis have shown that competitive balance in sport is correlated with attendance demand (e.g. Meehan, Nelson and Richardson, 2007;Rascher and Solmes, 2007). If this is correct, then any decline in competition may result in reduced income from gate receipts.…”
Section: Theoretical Considerations and Practical Relevancementioning
confidence: 99%